Aβ-induced degradation of BMAL1 and CBP leads to circadian rhythm disruption in Alzheimer’s disease - Song, Hyundong (Mol Neurodegener, 2015)
BACKGROUND: Patients with Alzheimer’s disease (AD) frequently experience disruption of their circadian rhythms, but whether and how circadian clock molecules are perturbed by AD remains unknown. AD is an age-related neurological disorder and amyloid-β (Aβ) is one of major causative molecules in the pathogenesis of AD. RESULTS: In this study, we investigated the role of Aβ in the regulation of clock molecules and circadian rhythm using an AD mouse model. These mice exhibited altered circadian behavior, and altered expression patterns of the circadian clock genes, Bmal1 and Per2. Using cultured cells, we showed that Aβ induces post-translational degradation of the circadian clock regulator CBP, as well as the transcription factor BMAL1, which forms a complex with the master circadian transcription factor CLOCK. Aβ-induced degradation of BMAL1 and CBP correlated with the reduced binding of transcription factors to the Per2 promoter, which in turn resulted in disruptions to PER2 protein expression and the oscillation of Per2 mRNA levels. CONCLUSIONS: Our results elucidate the underlying mechanisms for disrupted circadian rhythm in AD. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13024-015-0007-x) contains supplementary material, which is available to authorized users.